2020
DOI: 10.2147/amep.s275182
|View full text |Cite
|
Sign up to set email alerts
|

<p>Academic Achievements in National Competence Assessment Among Health Extension Students in Regional Health Science Colleges, Amhara Region, Ethiopia</p>

Abstract: Background: The national competency assessment (NCA) is a strategy with the objective of creating a competent, motivated, adaptable and innovative workforce in Ethiopia. However, of all the students that had taken the NCA, below average students had passed the assessment in the study settings. Therefore, this study aimed to assess the level of academic achievements of health extension students (HESs) and identify the influencing factors that contribute to the failure of HESs on NCA in the study settings. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…14 Previous study done among graduating diploma health extension students in Amhara region health sciences colleges in northern Ethiopia revealed that only 31.7% passed national competency assessment. 15 Similarly, 31.6% of midwifery graduates from different Ethiopian universities passed standard for graduation that indicates a great gap between the country's demand for competent health workforce and effectiveness of their clinical education. 16 In addition, only 24.5% of 3rd and 4th year nursing students of Mettu University in western Ethiopia achieved their clinical learning outcomes while year of study and conduciveness of clinical placement predicted positively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Previous study done among graduating diploma health extension students in Amhara region health sciences colleges in northern Ethiopia revealed that only 31.7% passed national competency assessment. 15 Similarly, 31.6% of midwifery graduates from different Ethiopian universities passed standard for graduation that indicates a great gap between the country's demand for competent health workforce and effectiveness of their clinical education. 16 In addition, only 24.5% of 3rd and 4th year nursing students of Mettu University in western Ethiopia achieved their clinical learning outcomes while year of study and conduciveness of clinical placement predicted positively.…”
Section: Introductionmentioning
confidence: 99%
“…20 Overall, previous studies done in the country revealed poor achievement of clinical competency among different health science departments. [15][16][17] But the achievement of clinical learning outcomes is the determinant of the overall success of both nursing and midwifery educational programs. 21 Thus, this study aimed to determine the status of achievement of clinical learning outcomes and associated factors among midwifery and nursing students of Jimma University after resumption of educational program following lockdown for COVID-19.…”
Section: Introductionmentioning
confidence: 99%